DIAGNOSTIC ACCURACY OF RAPID FOSFOMYCIN NP TEST FOR DETECTION OF FOSFOMYCIN RESISTANCE IN ESCHERICHIA COLI IN A TERTIARY CARE HOSPITAL IN PAKISTAN - Yunus, Faryal; Hussain, Ashfaq; Mirza, Irfan Ali; Hanif, Faisal; Hussain, Wajid; Satti, Luqman; Khursheed , Umar (Journal of Ayub Medical College Abbottabad, 2021)
Background: Emergence of resistance among Escherichia coli (E.coli) isolates against therapeutic options for UTIs (Urinary tract infections) has led to renewed interest in older antibiotics like Fosfomycin. In this study we evaluated diagnostic accuracy of Rapid Fosfomycin NP test based on glucose metabolism for rapid Fosfomycin susceptibility testing among urinary E.coli isolates. Methods: In a cross-sectional validation study conducted in the Microbiology Department, Armed Forces Institute of Pathology, Rawalpindi, Pakistan from 15th March to 15th September 2020, 149 consecutive urine specimens were included as per selection criteria. Rapid Fosfomycin NP test was performed as per protocol of Nordmann P et al on urinary E.coli isolates for detection of Fosfomycin resistance and results were compared with reference modified Kirby-Bauer disk diffusion method. Results: Out of total 149 E.coli isolates from 149 urine specimens, 80 were classified as Fosfomycin susceptible and 69 as Fosfomycin resistant by reference disk diffusion method. Sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of rapid Fosfomycin NP test was found to be 94.2%, 98.75%, 98.48%, 95.2% and 96.64%, respectively. In our study reliable results were achieved after 2.5 hours of incubation. Conclusion: The rapid Fosfomycin NP test is valid and user-friendly technique which can be performed with minimal technical expertise. It is less time consuming than disk diffusion and E-test strips and easy to perform as compared to agar dilution method. It can be useful as alternative to agar dilution in urinary E.coli isolates which would help in selecting appropriate therapeutic option for UTIs.